Empirical study on the leadership structure and working capital — based on the moderating effect of internal control - Changxiang, Huang; Hamdan, Sunita Lylia Binti; Sani, Noridayu Binti Abdullah (Asian Economic and Financial Review, 2025)
The purpose of this study is to examine the relationship between CEO-chairman separation, internal control, and working capital. To achieve this research objective, the study employs the least squares method, using a sample of 22,719 observations from A-share listed companies on the Shanghai and Shenzhen Stock Exchanges from 2007 to 2019. The main hypotheses are tested through the coefficients of a multiple linear regression equation. The results of this study indicate that the implementation of role separation between the CEO and Chairman can effectively reduce the cash cycle and improve the efficiency of working capital management. Furthermore, good internal controls not only help to improve the effectiveness of managing working capital, they also help to moderate the connection between role separation and the effectiveness of managing working capital. Furthermore, compared with state-owned enterprises, private enterprises demonstrate a more significant impact of internal control effectiveness on improving working capital management efficiency. This further highlights the critical role of internal control in the working capital management of private enterprises.